PENDIDIKAN HOLISTIK JIDDU KRISHNAMURTI - Krisna Sukma Yogiswari (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2018)
Education is a strategic way in relation to individual efforts to develop their po- tential. Learning strategies continue to be improved in order to achieve the goals of education itself. Holistic education is the focus of the study of activists and observers of education. The holistic education model emphasizes the importance of psychomotor behavior and overall activity. The development of cognitive abil- ities related to academic values is still considered important although it is not the sole main objective to be sharpened. The philosophy of Jiddu Krishnamurti that teaches humanism is also a supporter of holistic education.